Implementasi Program Islamic Boarding School sebagai Upaya Peningkatan Imtaq dan IPTEK dalam Pengembangan Potensi Spiritual Peserta Didik - Fatimatuzzahroh, Fatimatuzzahroh; Eri Kusumaningrum, Desi; Bambang Sumarsono, Raden; Triwiyanto, Teguh (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
The rapid advancement of science and technology (Iptek) in the digital era requires educational institutions to focus not only on academic achievement but also on strengthening students’ faith and piety (Imtaq). However, previous studies have predominantly emphasized cognitive development without systematically integrating spiritual dimensions into educational programs. This study aims to describe and analyze the implementation of the Islamic Boarding School (IBS) program as an effort to enhance Imtaq and Iptek in developing students’ spiritual potential at MTs Negeri 1 Kebumen. Employing a qualitative approach with a case study design, data were collected through interviews, observations, and documentation, and analyzed using data condensation, data display, and conclusion drawing techniques. The findings reveal that the IBS program is implemented through curriculum integration combining Islamic and digital literacy values, habitual religious activities, and additional services that support spiritual and intellectual formation. Teachers and IBS supervisors play crucial roles not only as educators but also as character facilitators and coordinators of religious activities. Supporting factors include parental involvement, a conducive school environment, and adequate facilities, while inhibiting factors stem from gadget use, student fatigue, and peer influence. This study concludes that the IBS program significantly contributes to balancing Imtaq and Iptek development and enriches the model of spiritual-integrated education in Islamic schools. Theoretically, the study reinforces the concept of holistic pesantren-based education that remains relevant in the digital context